Common Features of Regulatory T Cell Specialization During Th1 Responses - Littringer, Katharina; Moresi, Claudia; Rakebrandt, Nikolas; Zhou, Xiaobei; Schorer, Michelle; Dolowschiak, Tamas; Kirchner, Florian; Rost, Felix; Keller, Christian W.; McHugh, Donal; LeibundGut-Landmann, Salomé; Robinson, Mark D.; et al. (Frontiers in Immunology, 2018)
CD4+Foxp3+ Treg cells are essential for maintaining self-tolerance and preventing excessive immune responses. In the context of Th1 immune responses, co-expression of the Th1 transcription factor T-bet with Foxp3 is essential for Treg cells to control Th1 responses. T-bet-dependent expression of CXCR3 directs Treg cells to the site of inflammation. However, the suppressive mediators enabling effective control of Th1 responses at this site are unknown. In this study, we determined the signature of CXCR3+ Treg cells arising in Th1 settings and defined universal features of Treg cells in this context using multiple Th1-dominated infection models. Our analysis defined a set of Th1-specific co-inhibitory receptors and cytotoxic molecules that are specifically expressed in Treg cells during Th1 immune responses in mice and humans. Among these, we identified the novel co-inhibitory receptor CD85k as a functional predictor for Treg-mediated suppression specifically of Th1 responses, which could be explored therapeutically for selective immune suppression in autoimmunity.